2010
DOI: 10.1007/s00408-009-9225-8
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Levels of Circulating Endothelial Progenitor Cells During Exacerbations of COPD

Abstract: Cardiovascular morbidity and mortality is increased in patients with chronic obstructive pulmonary disease (COPD). Reduced levels of circulating endothelial progenitor cells (EPCs) are associated with increased risk of death in patients with stable coronary artery disease (CAD). Likewise, during acute events of CAD, the number of circulating EPCs increases under the influence of vascular endothelial growth factor (VEGF) and systemic inflammation. Abnormal levels of circulating EPCs have been reported in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 28 publications
0
42
1
Order By: Relevance
“…The potent pro-angiogenic factor VEGF is a known chemo-attractant of EPCs. Levels of VEGF-A have been correlated to the number of CD34+ cells (progenitor cell marker) in the plasma of COPD patients [62]. The increased presence and persistence of circulating EPCs in patients with asthma and COPD could be significant to the increased vasculature seen in these remodelled airways.…”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%
“…The potent pro-angiogenic factor VEGF is a known chemo-attractant of EPCs. Levels of VEGF-A have been correlated to the number of CD34+ cells (progenitor cell marker) in the plasma of COPD patients [62]. The increased presence and persistence of circulating EPCs in patients with asthma and COPD could be significant to the increased vasculature seen in these remodelled airways.…”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%
“…By contrast, Sala et al (2010) reported a positive relationship between plasma VEGF levels and the percentage of circulating EPCs (r = 0.51, p = 0.003) during COPD exacerbations. However, this correlation was not seen in stable COPD patients (r = 0.20, p = 0.22) (Sala et al 2010).…”
Section: Discussionmentioning
confidence: 84%
“…In patients with rheumatoid arthritis, VEGF and basic fibroblast growth factor levels do not correlate with EPC numbers (Grisar et al 2005). By contrast, Sala et al (2010) reported a positive relationship between plasma VEGF levels and the percentage of circulating EPCs (r = 0.51, p = 0.003) during COPD exacerbations. However, this correlation was not seen in stable COPD patients (r = 0.20, p = 0.22) (Sala et al 2010).…”
Section: Discussionmentioning
confidence: 93%
“…However, as the authors only used markers of HSCs and did not use any specific endothelial marker such as kinase-insert domain receptor (KDR), they could not infer whether EPCs along with HSCs were reduced in COPD patients. In the same year, a cross-sectional study by Fadi 30 . The results showed that the levels of EPC were higher in ECOPD (n = 35) than patients with stable COPD (n = 44) and healthy controls (n = 20).…”
Section: Copd and Endothelial Dysfunctionmentioning
confidence: 99%
“…In COPD, few studies to date have investigated the number of circulating progenitor cells [22][23][24][28][29][30][31] . While most of the studies indicate lower levels of EPCs in COPD patients compared with controls [22][23][24]31 , others do not find a significant difference 28,30 .…”
mentioning
confidence: 99%